Immunologic Rejection of Transplanted Retinal Pigmented Epithelium: Mechanisms and Strategies for Prevention - Petrash, Carson C.; Palestine, Alan G.; Canto-Soler, M. Valeria (Frontiers in Immunology, 2021)
Replacement of dysfunctional retinal pigmented epithelium (RPE) with grafts derived from stem cells has the potential to improve vision for patients with retinal disorders. In fact, the potential is such that a great number of groups are attempting to realize this therapy through individual strategies with a variety of stem cell products, hosts, immunomodulatory regimen, and techniques to assess the success of their design. Comparing the findings of different investigators is complicated by a number of factors. The immune response varies greatly between xenogeneic and allogenic transplantation. A unique immunologic environment is created in the subretinal space, the target of RPE grafts. Both functional assessment and imaging techniques used to evaluate transplants are susceptible to erroneous conclusions. Lastly, the pharmacologic regimens used in RPE transplant trials are as numerous and variable as the trials themselves, making it difficult to determine useful results. This review will discuss the causes of these complicating factors, digest the strategies and results from clinical and preclinical studies, and suggest places for improvement in the design of future transplants and investigations.